The Physicality of Writing in Paul Auster’s White Spaces and Winter Journal - François Hugonnier (Angles)
White Spaces is a hybrid piece of poetic prose marking Paul Auster’s literary rebirth. This matrix text, which served as an immediate response to Auster’s “epiphanic moment of clarity” during a dance rehearsal in New York, is an early experimentation with the physicality of writing. Words are steps. Verbs are motions. Facing the choreographer’s incapacity to put into words the December 1978 dance rehearsal, he began — step by step, word by word — to give in to silence, linguistic randomness and wandering. Auster suddenly realized that literary creation springs from physical commands rather than intellectual ones. Thirty years later, in Winter Journal, Paul Auster took up his exploration of the impersonal and tested the second-person narrative voice of his aging self. In both White Spaces and Winter Journal, the repetition of the binary rhythm of steps, breath, heartbeat, and the emphasis on doublings and symmetry widen the scope of Auster’s organic use of language. Speaking and writing require losing oneself to an interior music, as if the words were alive, freely animated and dictated to the writer by his own body. Speech, which parallels the world seen, is propelled by its own flow. Sensory limitations and the inadequacy of language, which had led Auster to a poetic dead-end, are in turn deplored and celebrated. As suggested in Winter Journal, language registers negativity as indirectly as the body integrates trauma. Shifting from pleasure to pain, the body exhibits the wounds of the past. Repeatedly, these cyclical works focus on feeling, falling and failing. Hence the aim of this paper is to highlight Auster’s metaphysical quest and aesthetic obsessions, which put the body’s functions and failures at the core of the writing process.